DAMPAK PROCESS-ORIENTED GUIDED-INQUIRY LEARNING (POGIL) TERHADAP PENGETAHUAN METAKOGNITIF SISWA PADA TOPIK ASAM-BASA - Ardhana, Ivan Ashif (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Aim of this research is to investigate different impact of Process-Oriented Guided-Inquiry Learning (POGIL) and verification as learning approach at senior high school students? metacognitive knowledge grade XI program IPA on acid-base topic. Research design used was quasi experimental. Hypothesis testing uses t-test with 5% (0,05) significance utilizing SPSS 21 application. Results show that (1) there is significance difference of students? metacognitive knowledge that is taught by POGIL approach and verification, and (2) students that are taught by POGIL approach give better answer?s pattern of declarative, procedural, and conditional knowledge than students that are taught by verification approach.